IDENTIFIKASI FAKTOR PENYEBAB PEMBENGKAKAN BIAYA (COST OVERRUN) PADA PROYEK PEMBANGUNAN : STUDI KASUS : GEDUNG JASAMARGA SEMARANG - Umi Rahayu (JERA : Journal of Engineering Research and Application, 2024)
Thel Jasa Marga Bulilding, as a complelx construlction projelct involving variouls stagels, matelrials and labor, is not frelel from thel risk of cost ovelrrulns. In ordelr to mitigatel thel risk of cost ovelrrulns and improvel ovelrall projelct managelmelnt, it is important to carry oult an in-delpth analysis of thel factors caulsing cost ovelrrulns on thel Jasa Marga Bulilding projelct. Throulgh in-delpth analysis of rellelvant variablels, it is hopeld that thel relsullts of this relselarch will providel valulablel insights for construlction practitionelrs, projelct managelrs and othelr rellateld partiels in ovelrcoming cost ovelrruln problelms and increlasing thel elffelctivelnelss of construlction projelct managelmelnt in thel fultulrel